THE POTENTIAL USE OF BIOMASS (SAPINDUS MUKOROSSI) FOR PRODUCTION OF VALUABLE PRODUCTS - Rifayat Ashraf, Huang Shen Chua, Kiat Moon Lee, Mohammed J.K.Bashir, Thing Thing Goh, Ainon Shakila Shamsuddin (International Journal of Modern Agriculture, 2020)
Civilization has been improving since the beginning of humanity, utilizing all those natural resources. When natural resources are used as a source of any form of energy, called biomass. Some biomasses are generated from waste in the household. These kinds of products can be useful when they are treated with pyrolysis treatment, biological treatment and other thermal degradation processes. Biomass needs to be dried before going to the thermal process or pyrolysis process. According to analysis, when the time can vary significantly by 3, 6, 9, and 12 hours, temperature ranges of 150°C, 200°C and 250°C can be chosen. The temperature of the reactor can be chosen from 500°C to 550°C, which provides a great amount of bio-oil. The heating rate will vary between 5°C/min, 10°C/min and 20°C/min. These processes can convert the most unproductive products into real valuable products. Soapnuts (Sapindus Mucorossi) is considered as one of the most insubstantial biomasses that has been researched and executed in a limited manner, no other use than dumping. It is to be noted that ‘Soap nuts’ are a great source of bio-oil, biochar and biogas (Syngas) that can be converted by a fast pyrolysis process. A small amount of “Erucic” acid present in soap nuts which is absent to bio-oil produced by another biomass. This “Erucic” acid improved the quality and distinguish it from others as unique characteristic. Some waste management treatment has also been compared in this research. The yield from the pyrolysis process can produce not only bio-oil but also other beneficial chemical elements. The main focus of this research is on the bio-oil which is extracted from soap nuts (Sapindus Mucorossi). Overall comparison of the soap nut with other nonedible bio-oil from similar biomass is provided.